Biodiesel from oil produced in vegetative tissues of biomass – A review. (April 2021) - Singh, Ramkrishna; Arora, Amit; Singh, Vijay
Highlights: Genetic engineering enables lipid accumulation in vegetative tissues. Transgenic crops derived lipid are alternative for oilseed lipid for biodiesel production. Oil extraction technologies suitable for vegetative biomass are proposed. Different strategies have been presented for improving feedstock quality. Pathways for conversion of transgenic crops derived lipid into biodiesel are proposed. Abstract: Biodiesel is a green, renewable alternative to petroleum-derived diesel. However, using vegetable oil for biodiesel production significantly challenges the food security. Progress in metabolic engineering, understanding of lipid biosynthesis and storage have enabled engineering of vegetative tissues of plants such as sugarcane, sorghum, and tobacco for lipid production. Such sources could be cultivated on land resources, which are currently not suitable for row crops. Besides achieving significant lipid accumulation, it is imperative to maintain the fatty acid and lipid profile ideal for biodiesel production and engine performance. In this study, genetic modifications used to induce lipid accumulation in transgenic crops and the proposed strategies for efficient recovery of oil from these crops have been presented. This paper highlights that lipids sourced from vegetative biomass in their native form would pose significant challenges in biodiesel production. Therefore, different strategies have been presented for improving feedstock quality to achieve high-quality biodiesel production.